Gains in grain yield of early maize cultivars developed during three breeding eras under multiple environments - Badu-Apraku, Baffour; Fakorede, M.A.B.; Oyekunle, M.; Yallou, G.C.; Obeng-Antwi, K.; Haruna, A.; Usman, I.; Akinwale, R. (Wiley, 2015)
Maize (Zea mays L.), an important staple crop in West and Central Africa (WCA), has enormous potential to reduce food insecurity in this subregion. Research covering three periods or eras of breeding has been conducted to develop cultivars resistant/tolerant to three maize stress factors: Striga parasitism, drought, and low soil nitrogen. A study was conducted under optimal or natural growing environments at 35 locations in WCA for 2 yr to determine genetic improvement in grain yield of the maize cultivars developed during the three breeding periods: 1988–2000 (period 1), 2001–2006 (period 2), and 2007–2010 (period 3). The average rate of increase in grain yield under optimum growing conditions was 40 kg ha?1 yr?1 with a genetic gain of 1.3% yr?1, which was slightly higher than the gain of 30 kg ha?1 yr?1, an annual genetic gain of 1.2% across 16 stress environments. It was concluded that substantial improvement in the yield potential of early maize under relatively nonstress environmental conditions has been made in this subregion by breeding for stress tolerance during the past three decades. The varieties EV DT-W 2008 STR, 2009 DTE-Y STR Syn, and TZE-W DT C2 STR, all from the latest era of improvement, were identified as the highest yielding and most stable cultivars and should be promoted to contribute to food security in this subregion.